Steady-State Security and Frequency Stability Assessment of the Ambon Power System Expansion Plan - RADITYA JAYESWARA; CANDRA FEBRI NUGRAHA; MUHAMMAD ZAKI MUHARRAM; DAVID DANINDRA ADI RAJASA (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
This study evaluates the steady-state security and frequency stability of the Ambon power system expansion plan based on the 2025–2034 RUPTL. The evaluation considers generation additions and the development of the 150 kV transmission network. Simulations were performed using DIgSILENT PowerFactory through power flow, N-1 contingency, three-phase short-circuit, and frequency stability analyses. The results show that all bus voltages remain within the allowable limits, with the lowest value of 0.992 p.u. The maximum line loading reaches 25.86% under normal conditions and 43.75% during the N-1 contingency. The maximum short-circuit current is 8.7 kA, while the lowest frequency nadir is 49.725 Hz. These results indicate that the Ambon power system expansion plan based on the RUPTL satisfies the technical security criteria.